2024
DOI: 10.1038/s41467-024-48106-6
|View full text |Cite
|
Sign up to set email alerts
|

Diet-omics in the Study of Urban and Rural Crohn disease Evolution (SOURCE) cohort

Tzipi Braun,
Rui Feng,
Amnon Amir
et al.

Abstract: Crohn disease (CD) burden has increased with globalization/urbanization, and the rapid rise is attributed to environmental changes rather than genetic drift. The Study Of Urban and Rural CD Evolution (SOURCE, n = 380) has considered diet-omics domains simultaneously to detect complex interactions and identify potential beneficial and pathogenic factors linked with rural-urban transition and CD. We characterize exposures, diet, ileal transcriptomics, metabolomics, and microbiome in newly diagnosed CD patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…Notably, increased dietary Mn intake was recently identified as a protective against Crohn’s disease; while at the population-level, the intake of dietary Mn has decreased by >40% in the last 15 years. 74, 75 Regulation of de novo UDP-GlcNAc availability is dependent on the hexosamine biosynthetic pathway that integrates the metabolism of carbohydrates, amino acids, fat, and nucleotides, with supply also determined by salvage pathways. Supply of GlcNAc in the gut may also be determined by resident microbiota and degradation of dietary-derived monosaccharides and glycopeptides.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, increased dietary Mn intake was recently identified as a protective against Crohn’s disease; while at the population-level, the intake of dietary Mn has decreased by >40% in the last 15 years. 74, 75 Regulation of de novo UDP-GlcNAc availability is dependent on the hexosamine biosynthetic pathway that integrates the metabolism of carbohydrates, amino acids, fat, and nucleotides, with supply also determined by salvage pathways. Supply of GlcNAc in the gut may also be determined by resident microbiota and degradation of dietary-derived monosaccharides and glycopeptides.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and, more recently, dietary and multi-omics studies (i.e., Braun et al. 4 ) aim to capture the contribution of exposure to CD pathogenesis and the related gut microbial alterations. Many previous studies have shown alterations in the gut microbiome, but the specific bacteria involved have varied between studies.…”
Section: Main Textmentioning
confidence: 99%